Blood-based molecular signature of Alzheimer's disease via spectroscopy and metabolomics - Habartová, Lucie; Hrubešová, Kateřina; Syslová, Kamila; Vondroušová, Jana; Fišar, Zdeněk; Jirák, Roman; Raboch, Jiří; Setnička, Vladimír (Clinical biochemistry, 2019)
OBJECTIVES: With over 35 million cases worldwide, Alzheimer's disease (AD) represents the main cause of dementia. The differentiation of AD from other types of dementia is challenging and its early diagnosis is complicated. The established biomarkers are not only based on the invasive collection of cerebrospinal fluid, but also lack sufficient sensitivity and specificity. Therefore, much current effort is aimed at the identification of new biomarkers of AD in peripheral blood. DESIGN AND METHODS: We focused on blood-based analyses using chiroptical spectroscopy (Raman optical activity, electronic circular dichroism) supplemented with conventional vibrational spectroscopy (infrared, Raman) and metabolomics (high-performance liquid chromatography with a high-resolution mass detection). RESULTS: This unique approach enabled us to identify the spectral pattern of AD and variations in metabolite levels. Subsequent linear discriminant analysis of the spectral data resulted in differentiation between the AD patients and control subjects. CONCLUSIONS: It may be stated that this less invasive approach has strong potential for the identification of disease-related changes within essential plasmatic biomolecules and metabolites.
Keywords: senioři; Spectrum Analysis, Raman; cirkulární dichroismus; senioři nad 80 let; metabolomika; Metabolomics; krevní proteiny; diskriminační analýza; Blood Proteins; Middle Aged; Alzheimer Disease; Discriminant Analysis; Aged, 80 and over; Humans; Circular Dichroism; biologické markery; lidé středního věku; Alzheimerova nemoc; Biomarkers; Aged; Ramanova spektroskopie; lidé